KOMUNIKASI KONSULTATIF PENYULUH AGAMA ISLAM DI DAERAH PERBATASAN KALIMANTAN BARAT - Bob Andrian (INSTITUT AGAMA ISLAM NEGERI METRO, 2019)
Religious Intructor is one of the spearheads of the government, especially the Ministry of Religion, to provide guidance and counseling to the community. Islamic Religius Instructors are also a profession that has a significant role in communicating Islamic values ​​to the wider community, especially Muslim communities in border areas that have limited access to urban centers. The person is called an Instructor, both functional, honorary religious counselors and someone who carries out voluntary guidance and counseling (Volunteer) work. In addition, religious counselors are also mentioned by some experts that